Performance analysis of LEO mobile satellite systems with DS-CDMA and FDMA/TDMA - Fu, Hongyi. (2008)
In order to realize comprehensive personal communication services (PCS), mobile satellite systems play an essential role in a global infrastructure. In a comparison of the satellite systems adopting geostationary and non-geostationary orbits, low earth orbit (LEO) constellations have attracted greater attention because of their small propagation delay and high link margin. As a crucial issue of system design, multiple access performance of LEO satellite systems is analyzed in this thesis.